2021
DOI: 10.31557/apjcp.2021.22.4.1279
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Aging-Related Polymorphisms with Susceptibility to Lung Cancer: A Case-Control Study in a Japanese Population

Abstract: Background: Telomere length is associated with cancer as well as aging. Telomerase reverse transcriptase (TERT), telomere RNA component (TERC) and oligonucleotide/oligosaccharide-binding fold containing 1 (OBFC1) are known to be involved in telomere length regulation. The tumor suppressor p53 (TP53), which has been shown to interact with tumor protein p53-binding protein 1 (TP53BP1), is implicated in the response to telomere shortening and aging. Polymorphisms in the TP53 and TP53BP1 genes are associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Two proteasome-related proteins, namely PSMA3 and PSMA6, were hub genes in MMI-MHCI-SP, and their higher expression in patients suggested that the host may utilize proteasomes to eliminate disease-related proteins (Fig 9C ). Three hub genes (TP53BP1, LMNA and NONO) in HMI-MHCI-SP are involved in DNA damage repair and thus maintain the genome stability [64][65][66] (Fig 9D). Existing studies reported that overexpression of estrogen receptor (e.g.…”
Section: Plos Computational Biologymentioning
confidence: 99%
“…Two proteasome-related proteins, namely PSMA3 and PSMA6, were hub genes in MMI-MHCI-SP, and their higher expression in patients suggested that the host may utilize proteasomes to eliminate disease-related proteins (Fig 9C ). Three hub genes (TP53BP1, LMNA and NONO) in HMI-MHCI-SP are involved in DNA damage repair and thus maintain the genome stability [64][65][66] (Fig 9D). Existing studies reported that overexpression of estrogen receptor (e.g.…”
Section: Plos Computational Biologymentioning
confidence: 99%